The Study Regarding Instructional Technology Use: Perspective Of Graduate-Level Students (Journal of Namibian Studies : History Politics Culture, 2023)
The main objective of this research was to determine the use of instruction technology and the perspective of graduate-level students in south Punjab. The study population comprised all graduate-level students in the universities of Dera Ghazi Khan. The Researcher conducted the survey to collect the data and personally accessed the participants. Data was analyzed by using SPSS version 20.0. For data analysis mean, percentage and t-test were used. After analysis, research found that instructional technology improves the teaching and learning process. It was also discovered that Internet access was supplied in teacher training institutes. The teachers noted that even though using instructional technology is expensive, it improves the quality of education.  It was concluded that the usage of instructional technology stimulates pupil engagement in academics.